Creating and governing cultural heritage in the European Union : the European heritage label /: the European heritage label. (2020) - Lähdesmäki, Tuuli; Čeginskas, Viktorija L. A; Kaasik-Krogerus, Sigrid; Mäkinen, Katja; Turunen, Johanna
No abstract available